1996
DOI: 10.1207/s15327906mbr3101_5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Bias and Mean Squared Error in Parameter Estimates of Interaction Effects: Moderated Multiple Regression versus Error-in-Variables Regression

Abstract: The results of moderated multiple regression (MMR) are highly affected by the unreliability of the predictor variables (regressors). Errors-in-variables regression (EIVR) may remedy this problem as it corrects for measurement error in the regressors, and thus provides less biased parameter estimates. However, little is known about the properties of the EIVR estimators in the moderator variable context. The present study used simulation methods to compare the moderator variable detection capabilities of MMR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Other Meta-Analyses Meta-analysis of the Five Factor Model validities in U.S. studies from 1992 through 1997 produced results similar to past U.S. metaanalyses (Anderson & Viswesvaran 1998), but meta-analyses involving only European samples produced somewhat different results (Salgado 1997a(Salgado , 1998. Both conscientiousness and emotional stability correlated positively with job performance across occupational groups, and both contributed incremental variance beyond general mental ability in predicting overall job performance.…”
Section: Core Self-evaluationmentioning
confidence: 63%
See 1 more Smart Citation
“…Other Meta-Analyses Meta-analysis of the Five Factor Model validities in U.S. studies from 1992 through 1997 produced results similar to past U.S. metaanalyses (Anderson & Viswesvaran 1998), but meta-analyses involving only European samples produced somewhat different results (Salgado 1997a(Salgado , 1998. Both conscientiousness and emotional stability correlated positively with job performance across occupational groups, and both contributed incremental variance beyond general mental ability in predicting overall job performance.…”
Section: Core Self-evaluationmentioning
confidence: 63%
“…Error variance in the independent variables affects differential prediction (Terris 1997), and errors-in-variables regression addresses this problem. Errors-invariables regression detected differential prediction more accurately than moderated multiple regression when reliability coefficients were Ͼ0.65 and sample sizes were Ͼ250 (Anderson et al 1996).…”
Section: Evaluation Of Selection Systems Differential Predictionmentioning
confidence: 93%
“…EIV regression also avoids some of the difficulties, such as convergence problems and offending estimates, that may arise when SEM techniques are used with complex models involving a large number of parameters (McDonald et al, 2005). Anderson, Stone-Romero, and Tisak (1996) showed that when interaction effects are tested, the estimates obtained using EIV were superior to those obtained employing ordinary least squares when both the sample size and the reliabilities of the predictors are high (above 250 and .65, respectively). Following standard procedure, we entered control variables and main effects in the first step and the interactive terms in the second.…”
Section: Test Of the Hypothesesmentioning
confidence: 98%
“…Recent research has questioned the validity of moderated or hierarchical multiple regression for interaction effects (Anderson, Stone-Romero, and Tisak, 1996;Jaccard and Wan, 1995). One of the most commonly cited problems associated with its use is that no moderating effects are often found.…”
Section: Testing For Moderator Effectsmentioning
confidence: 99%